Anodic Olefin Coupling Reactions: A Mechanism Driven Approach to the Development of New Synthetic Tools. (January 2016) - Moeller, Kevin D.
Abstract : Electrochemistry holds great potential as a tool for organic synthesis, but only if it is eventually adopted by "mainstream" organic chemists. Central to this development is an understanding of how organic chemists new to the area of electrochemistry can solve the problems inevitably encountered when exploring the use of an electrochemical method. In this manuscript, anodic olefin coupling reactions are used, along with a brief look at microelectrode arrays, as a backdrop to illustrate how basic concepts in physical organic chemistry frequently provide the key to the optimization of electrochemical reactions. In many cases, the "secret" to running a good electroorganic reaction is to do the organic chemistry well.